¿Puede hablar el pueblo? Educación, cultura y religiosidad popular en la revista Alternativa Latinoamericana - Guillermo Barón (Nuevo mundo - Mundos Nuevos, 2018)
The Alternativa Latinoamericana magazine was launched in the 1980s by the Argentine Ecumenical Movement. In it there was discussion, among other topics, of Popular Education and popular cultures and religiosities. As transverse to these issues the question of the intellectuals and their relationship with the people always arose. In this article we think about this issue from Michael Löwy and Robert Sayre´s hypothesis for a sociology of romanticism.